Mito e tragédia moderna: Orestes e Electra revisitados por Jean Giraudoux e Jean-Paul Sartre - Camino, Ana Luisa dos Santos (2012)
The French dramatists Jean Giradoux and Jean-Paul Sartre revisited the tragic Greek legacy and wrote the plays Électre (1937) and Les mouches (1943), respectively. Both authors, in their texts, drew from myths concerned with the tragic actions that took place in Agamemnon s palace: the murder of Clytemnestra by her children, Orestes and Electra. This research is centered on the analysis and comparison between Giraudoux s and Sartre s plays aiming at identifying in them the elements that indicate both the relations between myth (mythical thought) and logos (theoretical reason) and that between myth and modern tragedy. It also shows the fact that Sartre s text, maintains a dialog with the Greek legacy, and also offers a philosophical counterpoint to Giraudoux s play. In order to reach our goals we have examined the phenomenon of myth under the light of the philosophy of language, of the sacred, of anthropology and of literature, a theoretical basis that we tried to connect with the theories of Aristotle and Hegel about drama.